Analyzing the Effects of Kefir on the Gut Microbiota Strains in Alzheimer’s Patients - Vanessa Ellivia; Belinda Hariyanto; Erika Marceline Kwan; Angelyna Angelyna; Celestine Jovanka Tjahjadi; Andrea Benita Wiguna; Chelsy Angelline Wen; Junaida Astina (Indonesian Journal of Life Sciences, 2024)
Alzheimer's disease (AD) is a neurodegenerative disorder that progresses over time and slowly deprives patients of their memory, cognitive abilities, and eventually, capability to carry out even the simplest activities, and even affects the gut microbiota. Studies suggest changes in gut microbial diversity and abnormalities in the gut-brain axis are associated with AD. Probiotics, known for their numerous health benefits, are well recognized as one of the most effective prophylactic strategies against cognitive deterioration in AD. In order to grow, the gut microbiota needs nutrients including Lactobacilli and Bifidobacteria which are frequently linked to the therapeutic potential of kefir. It is proven to modulate the immune system and maintain gut health by modifying the gut microbiota, lowering the prevalence of inflammation as well as oxidative stress, which slows down the progression of AD. Thus, this review summarizes the possible benefits of probiotics, specifically, kefir, on the gut microbiota strains in Alzheimer’s patients. A literature search was conducted on scientific platforms using Google Scholar and PubMed. Given the inclusion criteria and the limitation on the publication year, 53 scientific articles were selected for further analysis. Keyword searches were limited to the following. (1) Alzheimer’s disease and/or (2) gut microbiota and/or (3) probiotics and/or (4) kefir. The findings of this study clarify the association between probiotics and AD in altering the gut microbiota by improving the proliferation of Lactobacillus and Bifidobacterium and subsequently slowing the progression of AD. Keywords: Alzheimer’s disease (AD); gut microbiota; probiotics; nutrients; bioactive compounds; kefir